Perencanaan Ulang Rumah Susun Tenaga Pendidik Universitas Gadjah Mada dengan Konsep Building Information Modeling (BIM) 5D - Yogi Hardianto; Ilham Muhammad Islam; Bambang Setiabudi; Asri Nurdiana (Jurnal Sipil dan Arsitektur, 2024)
The innovative development in construction technology has introduced a system called Building Information Modeling (BIM), which can facilitate processes from pre-construction to post-construction. Therefore, this research focuses on the redesign of the University of Gadjah Mada's Faculty Housing Tower using the integrated BIM concept, based on structural analysis with ETABS and modeling with Tekla Structures. The redesign is carried out according to SNI 2847-2019 for concrete building structures, SNI 1727-2020 for loading requirements, and SNI 1726-2019 for seismic resilience standards. This redesign produces a structural analysis to assess the structural feasibility of the building. The 3D design modeling is performed using Tekla software, which can generate 2D designs for Detail Engineering Design, as well as provide the necessary volume of work for cost estimation (RAB calculation). Additionally, the software allows for scheduling and work simulation. The redesign of the University of Gadjah Mada's Faculty Housing Tower results in a budget plan of IDR 24,274,962,257.00, calculated using Quantity Take Off from the Tekla Structures software. The scheduling and work implementation simulation for the structural components are also done using Tekla Structures software. The duration of this redesign project is estimated to be 4 months and 2 weeks, starting from the preparation phase to the completion of the roof structure